THE POTENTIAL OF MANNOPROTEIN EXTRACTED FROM CANDIDA APICOLA CELL WALL AS EMULSIFICATION AGENT - Sugiah SUGIAH; Roostita L. BALIA; Gemilang L. UTAMA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The constantly increasing world population, climate change, water depletion and soil degradation challenges the agriculture of the 21st century. Despite the fact that people practice farming for millennia, classical production methods are becoming less effective in the current conditions of growing demand. Thereby digital and communication technologies are designed to assist farmers to turn agriculture into high-tech industry. The introduction of Unmanned Aerial Vehicles is one of the most progressive and perspective trends in the agricultural sector. In addition to improving of efficiency, productivity and rationalization of the production processes, the technology is expected to bring a wide share of jobs opportunities. Drones are used for monitoring of the fields which may contribute to digitalization of agriculture. The high-quality of data collection and processing, engage the further development of the aircrafts, allowing them to become more multitasking in the future.